The Influence of Transformational Leadership on Employee Performance Through Job Satisfaction as an Intervening Variable at the Environmental Office of Sorong Regency, Southwest Papua Province - Roberthair Suripatty; Naomi Ormak; Jullie J. Sondakh; Hendra N. Tawas; Agus Supandi Soegoto; Hizkia Hendrik David Tasik (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the influence of transformational leadership on employee performance with job satisfaction as an intervening variable at the Environmental Agency of Sorong Regency, Southwest Papua. A quantitative approach was used with a census technique involving 47 employees, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. The results of the study indicate that transformational leadership has a positive and significant effect on job satisfaction (β = 0.612; p < 0.001) and employee performance (β = 0.397; p < 0.001). Job satisfaction also has a significant effect on employee performance (β = 0.458; p < 0.001) and partially mediates the relationship between transformational leadership and employee performance (β = 0.281; p = 0.002). The coefficient of determination shows that 67.4% of the variation in employee performance can be explained by transformational leadership and job satisfaction (R² = 0.674). These findings confirm the importance of transformational leadership practices that can enhance job satisfaction as a psychological mechanism in driving the performance of public sector personnel, particularly in the field of environmental management.